Content comparison of neck pain outcome measures using the international classification of functioning, disability and health. Issue 1 (12th November 2021) - Tiwari, Devashish; Clock, Christopher; Gore, Shweta; Alsalaheen, Bara
Abstract : The purpose of this study was to compare the content covered by existing neck pain measures based on the linkage to the International Classification of Functioning, Disability and Health (ICF) framework to examine the extent to which the existing measures represent ICF categories and to identify content gaps in existing measures that would inform further research. Ten commonly used measures were identified, and their content was linked to ICF categories using established coding systems. Two clinical experts reviewed every measure independently and identified the central meaningful concepts from individual items of each measure. A total of 177 concepts were identified from 193 items across 10 measures. Body functions were the most represented category across measures (23–64%). The representation of activities ranged from 14 to 61% whereas the representation of participation ranged from 6 to 31% across measures. The ProFitMap-Neck was the only measure that addressed the environmental factors. The ProFit-Map neck captured a majority of concepts from body structures and function and the neck outcome score captured maximum concepts from the activities and participation categories. A combination of ProFit-Map neck and Neck Outcome Score can be used with caution to obtain a more comprehensive assessment of the impact of neck pain on function, activities and participation.